P157 Evidence for clinical utility of extended HPV genotyping in persistence tracking and follow-up after abnormal results and colposcopy and test-of-cure. (1st November 2019) - Andrews, J
Abstract : Introduction/Background: An analysis of the body of science published recently about the clinical value of HPV genotyping in persistence tracking, follow-up of women with abnormal results, and follow-up after treatment of high-grade cervical intraepithelial neoplasia (CIN). Methodology: MedLine was searched from 2001 through 2019 for relevant studies. Hand-searching of retrieved article reference lists supplemented the search. Eligible studies included prospective studies of women and retrospective studies of residual specimens from women that were tested using HPV genotyping tests following an abnormal screening result, or colposcopy, or treatment for high-grade CIN. The reference standards were CIN2 or CIN3 or CIN2+ or CIN3+ or invasive cervical cancer. The timeframe for follow-up studies was at least 6-months to determine persistence; periods of 12-months and 24-months were accepted. This systematic review has been registered with PROSPERO. Cochrane risk of bias assessment was performed. GRADE methodology was used to establish quality and strength of evidence. Results: A PRISMA flow diagram is presented for this systematic review. 32 original research articles met inclusion and exclusion criteria. Reporting genotyping provides profound discrimination of both current and future CIN3+ risks, due to the differential risks of same genotype persistence versus new genotype infection. Within subjects with persistent same genotype, genotype reporting can discriminate risk by more than ten-fold. Genotyping could be utilized as follow-up type-specific persistence versus clearance, to support risk-based clinical decisions. Similar management for similar risk-discrimination is benchmarked. Conclusion: Based on quality-evaluated studies that met inclusion criteria, there is strong evidence for genotyping to distinguish same-genotype persistence versus clearance, to discriminate risk between same-genotype persistence versus new genotype infection, and support risk-based clinical action steps by the principle of equal management for equal risk. The role of same genotype persistence is critical to test-of-cure assessments. Models for different management paradigms are described. Disclosure: The speaker is a full time employee and Worldwide Medical Director for Women's Health & Cancer for BD Biosciences and Diagnostic Systems.